2002
DOI: 10.1109/mprv.2002.1012334
|View full text |Cite
|
Sign up to set email alerts
|

Project Aura: toward distraction-free pervasive computing

Abstract: A s the effects of Moore's law cause computing systems to become cheaper and more plentiful, a new problem arises: increasingly, the bottleneck in computing is not its disk capacity, processor speed, or communication bandwidth, but rather the limited resource of human attention. Human attention refers to a user's ability to attend to his or her primary tasks, ignoring system-generated distractions such as poor performance and failures. By exploiting plentiful computing resources to reduce user distraction, Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
284
0
14

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(299 citation statements)
references
References 11 publications
1
284
0
14
Order By: Relevance
“…The first is that it should enable the rapid development of both prototypes and target systems. While there are several existing platforms for ubiquitous computing ( [3,8,10] are examples), a software tool is required that facilitates the development of prototypes, while simultaneously providing the hooks for the target system.…”
Section: Related Literature and Goalsmentioning
confidence: 99%
“…The first is that it should enable the rapid development of both prototypes and target systems. While there are several existing platforms for ubiquitous computing ( [3,8,10] are examples), a software tool is required that facilitates the development of prototypes, while simultaneously providing the hooks for the target system.…”
Section: Related Literature and Goalsmentioning
confidence: 99%
“…There are a few ambitious middleware systems that were proposed as metaoperating systems capable of providing an integrated programming model for application developers [6,13,3,4,1]. Despite this considerable research effort, in recent years we have been witnessing a growing perception about a persistent gap between the promises of the area and its real achievements.…”
Section: Related Workmentioning
confidence: 99%
“…Particularly, the application programming model [3,5,10] (context-aware, service-oriented, user-centric, environment-centric, taskoriented, etc) is important for software planning and development phases. Roman et al [12] have identified six patterns that were required for all applications: multi-device utilization, user-centrism, run-time adaptation, mobility, contextsensitivity, and ubiquitous computing environment independence; and have identified five design guidelines: low-level system support, boot-strapping, scripting, application development and management support, and end-user support, which were considered essential to support ubiquitous computing environments and to increase number of application developers.…”
Section: Related Workmentioning
confidence: 99%
“…In ubiquitous computing environment, every service should have the characteristic of context-awareness [14]. In order to support this characteristic, the service provider is able to keep track the usage of a user.…”
Section: Consideration On Providing the Autonomous Servicementioning
confidence: 99%